A Hyperlipidic Diet Combined with Short-Term Ovariectomy Increases Adiposity and Hyperleptinemia and Decreases Cytokine Content in Mesenteric Adipose Tissue. (14th June 2015) - Neto, Nelson Inacio Pinto; Rodrigues, Maria Elizabeth Sousa; Hachul, Ana Claudia Losinskas; Moreno, Mayara Franzoi; Boldarine, Valter Tadeu; Ribeiro, Eliane Beraldi; Oyama, Lila Missae; Oller do Nascimento, Claudia Maria
Abstract : Four-week-old female Wistar rats were divided into two groups and fed a control diet (C) or a hyperlipidic diet (H) for 4 weeks. Rats from each group underwent ovariectomy (OVX) or sham surgery (SHAM). They received C or H for the next four weeks. The body weight gain (BW), food efficiency (FE), and carcass lipid content were higher in the OVX H than in the SHAM H. The OVX H exhibited a higher serum leptin level than other groups. IL-6, TNF- α, and IL-10 content of mesenteric (MES) adipose tissue was lower in the OVX H than in the OVX C. IL-6, TNF- α, and IL-10 content of retroperitoneal (RET) adipose tissue was lower in the SHAM H than in the SHAM C. The SHAM H showed decreased TG relative to the SHAM C. Similar results were obtained in relation to IL-6R α, TNFR1, TLR-4, and MyD88 contents in the MES and RET white adipose tissue among the groups. A hyperlipidic diet for 8 weeks combined with short-term ovariectomy decreases the cytokine content of MES adipose tissues but increases BW, enhancing FE and elevating serum leptin levels. These suggest that the absence of estrogens promotes metabolic changes that may contribute to installation of a proinflammatory process induced by a hyperlipidic diet.